El conocimiento del ocio en las sociedades de la periferia. Un análisis de los enfoques en la producción científica en Colombia (2012)
ABSTRACT: This paper presents some referents from a critical perspective to analyze some relevant issues in scientific production processes in leisure, recreation and free time. A framework which seeks to inquire on the conditions under which the knowledge of this subject in this field has been approached. This work is learning on the coloniality / modernity perspective, in power coloniality categories (Quijano, 2000), colonial difference (Mignolo, 2003), knowledge coloniality (Lander, 2000) and geopolitical knowledge (Mignolo in Walsh, 2003) proposing a framework analysis to leisure, recreation and free time in peripheral countries. Although this research contains six categories: Focuses, purposes, concepts, actors, places and tendencies, this paper only presents two of them: focuses and purposes, due to reasons of space.